Finance and Stochastics - Schweizer, Martin; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The purpose of Finance and Stochastics is to provide a high standard publication forum for research - in all areas of finance based on stochastic methods - on specific topics in mathematics (in particular probability theory, statistics and stochastic analysis) motivated by the analysis of problems in finance. Finance and Stochastics encompasses - but is not limited to - the following fields: - theory and analysis of financial markets - continuous time finance - derivatives research - insurance in relation to finance - portfolio selection - credit and market risks - term structure models - statistical and empirical financial studies based on advanced stochastic methods - numerical and stochastic solution techniques for problems in finance - intertemporal economics, uncertainty and information in relation to finance. Finance and Stochastics also publish surveys on financial topics of general interest if they clearly picture and illuminate the basic ideas and techniques at work, the interrelationship of different approaches and the central questions which remain open. Special issues may be devoted to specific topics in rapidly growing research ares. In summary, Finance and Stochastics serve as a publication platform for both theoretical and applied financial economists using advanced stochastic methods and researchers in stochastics motivated by and interested in applications in finance and insurance. Officially cited as: Finance Stoch History The first Editor-in-Chief was Dieter Sondermann (1996), who was succeeded by Martin Schweizer (2004).
Keywords: Finance; Economics, Mathematical; Probabilities; Economic theory; Quantitative Finance; Finance, general; Statistics for Business, Management, Economics, Finance, Insurance; Economic Theory/Quantitative Economics/Mathematical Methods; Probability Theory and Stochastic Processes